Influência de fatores de perda na eficiência de módulos fotovoltaicos em indústrias cerâmicas - Medeiros Filho, Álvaro Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
The growing use of photovoltaic technology for power generation is highlighted all over the country, providing autonomy in power generation with a lifespan of around 25 years, making it viable for civilians and businesspeople simultaneously. The introduction of photovoltaic systems in red ceramic industries is necessary. The high energy cost expense forces industries to seek the feasibility of installing photovoltaic systems, although the red ceramic industries provide a favorable environment for the accumulation of factors that cause loss of efficiency of the photovoltaic system. Thus, a case study is necessary. The present work aimed to correlate the observed loss factors with eventual losses in the efficiency of photovoltaic systems, and consequently a decrease in the electric power generation. Thus, the impact of these factors can be quantified, aiming at a possible reduction or eradication of them.
Artigo
Keywords: Módulo fotovoltaico; Energia solar; Energia sustentável; Photovoltaic module; Solar energy; Sustainable energy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA